MENGUNGKAP KEMBALI TAFSIR ATAS PANCASILA: DIBALIK PENCABUTAN KETETAPAN MPR TENTANG P4 - Winarno, Winarno (Faculty of Social Science, Universitas Negeri Semarang, 2012)
Pancasila is the foundation of the state of the Unitary Republic of Indonesia. The thought of Pancasila in state political lines are included in the MPR decree No. XVIII/MPR/1998 which also repeals provisions of Decree No. II/MPR/1978 about P4 (The Guidlines for Appreciating and Implementing Pancasila). The background of the issue the political determination is that the MPR decree on P4, the substance and implementation are no longer fit with the times. Pancasila charge in P4 is considered to have an expansion in interpretation of Pancasila. Implementation of the P4 upgrading program is considered to be the doctrinative, ineffective and spend a lot of costs. For the future, the interpretation of Pancasila should refer to the historical interpretation of the founding fathers and is developed through historical approach and juridical interpretations developed through legal approach. The implementation of Pancasila can be done with socialization through education.